2018
DOI: 10.1111/eos.12601
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported dry mouth among ageing people: a longitudinal, cross‐national study

Abstract: Focusing on Swedish and Norwegian cohorts of community‐dwelling older adults between age 65 and 70, this study aimed to identify predictors of the prevalence and incident cases of daytime and night‐time xerostomia. It was hypothesized that the prevalence increases with increasing age and is higher in women than in men and that the prevalence of persistent xerostomia and the 5‐yr‐incident cases are higher in people with consistent use of medication and need for health care. Of the Norwegian participants who com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
7
16
1
Order By: Relevance
“…Another factor associated with reduced salivation is aging. Research carried out in different age groups, clearly indicate the prevalence of problems with the secretion of saliva in elderly people [48,49]. However, it correlates with the more frequent taking of medicines due to the occurrence of diseases.…”
Section: Xerostomia: Etiology Of Salivary Glands Dysfunctionsmentioning
confidence: 99%
“…Another factor associated with reduced salivation is aging. Research carried out in different age groups, clearly indicate the prevalence of problems with the secretion of saliva in elderly people [48,49]. However, it correlates with the more frequent taking of medicines due to the occurrence of diseases.…”
Section: Xerostomia: Etiology Of Salivary Glands Dysfunctionsmentioning
confidence: 99%
“…In addition, social demographics and medical background characteristics may influence salivary conditions. Furthermore, it has been reported that women, in general, have lower salivary secretion rates than men (8), and hyposalivation is associated with female gender (9–11), use of xerogenic medications (9,12), increasing age (13), and chronic diseases, such as diabetes and Sjögren's syndrome (14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the prevalence of xerostomia increases with age (12,13,18,19). Xerostomia is reported more commonly in women (10,18–20), smokers (12,20), and individuals with symptoms of depression (9,20).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations